Effect of Sri Lankan bfack tea brew (Camellia sinensis) on hexabarbital induced sleep in mice - Ratnasooriya, W.D.; Fernando, T.S.P.; Madubashini, P.P. (My University, 2006)
Present study examined the effect of warm black tea brew/ infusion (BTB) of Camellia sinensis (L.) O. Kuntze (family: Theaceae) on sleep. The above was tested in hexabarbital mduced sleep model in mice using three doses (equivalent to 1.5.3. and9cups. 1 cup 170ml)ofSriLankanhighgrownI>ustgradeNo: 1 blackteaora single dose (equivalent to 9 cups) of green tea brew (GTB) of Japanese and Chinese varieties. The results showed tiiat black tea brew (BTB) significantly (P < 0.05) and dose-dependently prolonged the onset and shortened the duration of sleep. A similar effect was elicited with the high dose of GTBs but with a higher efficacy. Decaffeination of BTB suppressed the effects on the onset of sleep mduced by the normal BTB. It is concluded that Sri Lankan black tea disrupts sleep in mice possibly via dopamineigic, serotoninergic and nerve stimulant mechanisms.